2020
DOI: 10.1021/acsomega.0c02345
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of the Corrosion Inhibition Efficacy of a Dicationic Monomer and Its Polymer against API X60 Steel Corrosion in Simulated Acidizing Fluid under Static and Hydrodynamic Conditions

Abstract: N 1 , N 1 -diallyl- N 6 , N 6 , N 6 -tripropylhexane-1,6-diaminium chloride (NDTHDC) and its polymer poly( N 1 , N 1 -diallyl- N 6 , N 6 , N 6 -tripropylhexane-1,6-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…The inhibitor efficiency of N1,N1-diallyl-N6,N6,N6,N5tripropylhexane-1,6-diaminium (NDTHDC), for carbon steel in 15 percent HCl solution and found that poly-NDTHDC is better than NDTHDC in 1000 mg/L inhibitor and was used in weight loss, electrochemical, and surface testing techniques. The efficacy of the inhibition increased but afterwards fell at 60 °C of the combination (54). There are a few consumption control techniques to alter the materials viable, which incorporates cathodic insurance, (22,55,56); anodic insurance, (57,58) and alloying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The inhibitor efficiency of N1,N1-diallyl-N6,N6,N6,N5tripropylhexane-1,6-diaminium (NDTHDC), for carbon steel in 15 percent HCl solution and found that poly-NDTHDC is better than NDTHDC in 1000 mg/L inhibitor and was used in weight loss, electrochemical, and surface testing techniques. The efficacy of the inhibition increased but afterwards fell at 60 °C of the combination (54). There are a few consumption control techniques to alter the materials viable, which incorporates cathodic insurance, (22,55,56); anodic insurance, (57,58) and alloying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increased corrosive capability of diesel fuel over aqueous media can be referred to the presence of sulfur and aromatic compounds within its composition. These components are of withdrawing nature (Odewunmi et al 2020), however, with less ability than the corrosive sites in sulfuric acid. ……….……….…”
Section: Corrosion Inhibition Performancementioning
confidence: 99%
“…[11][12][13][14] In an acidizing application where 15 % HCl is mostly used, organic compounds containing heteroatom embedded in multiple-bonded cyclic compounds are reported to be effective corrosion inhibitors. [15][16][17] Two quinoxaline derivatives having thiazole motifs have been shown to impart inhibition efficiencies of � 96 % at 303 K at a concentration of 100 ppm. [18] The pyrido dipyrimidin-imidazolpropanoic acid and pyrano dipyrimidin-benzonitrile containing inhibitors were inhibited mild steel corrosion to the respective extent of 68 % and 63 % at 303 K. [19] The 2-hydrazinobenzothiazole decorated with carbohydrates inhibitors were demonstrated to impart inhibition efficiencies of � 80 % at 303 K at a concentration of 100 ppm.…”
Section: Introductionmentioning
confidence: 99%